Density Evaluation of Alkyl Ester from Different Types of Alcohol and Vegetable Oil - Dyah Retno Sawitri; Khusnul Azzam; Ani Chalwa Isnani; Darryl Al Husein (Equilibrium Journal of Chemical Engineering, 2026)
ABSTRACT. Alkyl ester, also known as biodiesel, is an alternative renewable energy source and is produced through the reaction of vegetable oil and alcohol. One of the important characteristics of biodiesel lies in the density value. This study evaluates the density value of alkyl esters from several raw materials. The raw materials used include palm oil and rice bran oil. In comparison, the types of alcohol used include methanol, ethanol, and isopropanol. The density values of palm oil ethyl ester and rice bran oil ethyl ester were measured at 30 – 100°C. The density measurement results were then compared with the simulation results using ASPEN Plus® software. The density of alkyl esters was measured over a temperature range of 30-100°C. The density measurements were then compared with the simulation results using ASPEN Plus® software. The measurement and simulation results showed that the density was higher in the order ethyl > methyl > isopropyl ester for palm oil. When viewed from the vegetable oil, the density of rice bran oil ethyl ester is higher than that of palm oil ethyl ester. The results of measuring biodiesel from rice bran oil and palm oil at 40°C show that only the isopropyl ester has a density that does not meet the quality requirements of biodiesel as defined by the Indonesian National Standard. Keywords:Biodiesel, Density, Palm oil, Rice bran oil